Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/19443994.2015.1058728
|View full text |Cite
|
Sign up to set email alerts
|

A Plug flow reactor model for UV-based oxidation of amoxicillin

Abstract: A B S T R A C TAmoxicillin was treated with UV and UV/H 2 O 2 processes, and the byproduct formation, mineralization and toxicity on Vibrio fischeri (a luminescent micro-organism) were monitored to satisfy environmental considerations. A plug flow cylindrical reactor (33 cm length and 1.75 cm radius) and a peristaltic pump (multifunctional speed pump) were used to perform the treatments. A UV lamp covered with a quartz protection was placed inside the reactor. The UV fluence rate was calculated with a chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Kidak [36], who also observed a first order reaction. In the alkaline medium, the reaction is a second order reaction (plot 1/C gave the best fitting results).…”
Section: Amoxicillin Oxidationmentioning
confidence: 94%
“…Kidak [36], who also observed a first order reaction. In the alkaline medium, the reaction is a second order reaction (plot 1/C gave the best fitting results).…”
Section: Amoxicillin Oxidationmentioning
confidence: 94%
“…Thus, the degradation of the β-lactam antibiotics can follow two routes, e.g. hydroxylation and opening of the β-lactam ring [44]. The ratio between these routes is influenced by the structure of the antibiotic and the nature of the catalyst.…”
Section: Degradation Of Antibioticsmentioning
confidence: 99%
“…The effect of pH on photocatalytic degradation/mineralization of antibiotics is better to be evaluated in a way that consider properties of antibiotics and photocatalyst of concern at different initial pH conditions as different pKa values of antibiotics are reported to be responsible for creating varying levels of surface interaction with the TiO 2 nanoparticles in the solution [20]while surface charge status for the antibiotics and TiO 2 by order at their optimum conditions can be described as; (+/+), (-/-) and (-/-) respectively.Several authors have already reported the influence of pH on TiO 2 -mediated photocatalytic degradation of AMX and found minimal influence in the near-neutral pH range.In this study, four pH values were investigated considering the surface charge change of TiO 2 that could affect the adsorption capacity thus the photocatalytic removal of CLRT and AMX antibiotics.…”
Section: Photocatalytic Degradationmentioning
confidence: 99%